Captain America/Black Panther. Flags of our fathers - Hudlin, Reginald (Marvel Worldwide, Inc., 2024)
The finest heroes of a generation -- New York's own Steve Rogers and King Azzuri of Wakanda -- fight together on the front lines of World War II! And Nick Fury and his Howling Commandos join them in combat with the nastiest Nazi villains in the Marvel Universe: Baron Strucker and the Red Skull! It's all-out action as Captain America and the Black Panther wage war against the Skull and his super-powered Nazi platoon -- but can their tenuous alliance withstand the onslaught of evil headed their way? Outmanned and outgunned, Cap and the Panther battle Master Man, Warrior Woman and White Gorilla! Plus: Delve into Wakandan history with the first chapter of RISE OF THE BLACK PANTHER!